Policy, Power, and Peace: Analyzing the Intersection of Defense Strategies and International Relations - Sarjito, Aris (Universitas Al-azhar Indonesia, 2025)
The evolving dynamics of international relations demand defense strategies that balance national security objectives with the broader goals of global stability and peacebuilding. This research explores the intersection of policy, power, and peace, focusing on how defense strategies integrate emerging technologies, align with international norms, and foster collaboration among states. Utilizing a qualitative approach, secondary data was analyzed, including policy documents, case studies, and academic literature, to examine the interplay between defense policies and international relations. Key findings reveal that aligning defense strategies with international frameworks fosters trust and cooperation, while integrating artificial intelligence and cyber capabilities reshapes global power dynamics by enhancing operational efficiency and geopolitical influence. Additionally, smaller states and regional actors play pivotal roles in peacebuilding, offering innovative approaches through diplomacy, inclusivity, and regional collaboration. The research concludes that sustainable defense strategies require a balance of military strength, ethical governance, and multilateral efforts to address contemporary global challenges. This study contributes to understanding the complexities of defense strategies within international relations, offering insights for policymakers aiming to achieve security and stability in a rapidly changing world.Keywords: defense strategies, emerging technologies, international relations, multilateral cooperation, peacebuilding